TRANSPARANSI PENILAIAN DENGAN METODE AUTHENTIC ASSESSMENT MELALUI APLIKASI WHATSAPP - Ismet Ismet (Jurnal Teknologi Informasi dan Pendidikan, 2020)
Abstract: The low response given by parents to the information conveyed through the whatsapp class group and the high desire of parents to find out the value of children in each test, encourages teachers to innovate to solve these problems. This research is a qualitative research that aims to inform the assessment process through the application of whatsapp with the authentic assessment method. The subjects of this study were students of class III SD Negeri 4 Metro Timur and parents of students who were members of the whatsapp class group of 26 people. Data collection is done by making observations with observation sheets and direct interviews. Submission of information is carried out by the teacher through WA starting from the assessment process, compiling an assessment rubric, evaluating both themes and subjects to carrying out improved grades or remedial. From the observations it is known that parents of students are very enthusiastic about the transparency of the assessment conducted by the teacher as much as 84% ​​of students' parents see and comment, 12% see and 4% do not see and do not comment. Parents come to understand the assessment process to show results, even to the improvement of grades. For this reason, the transparency of assessment will continue to be developed, not only focusing on exam results but also on the learning process.